Polymer‐Stabilized Micropixelated Liquid Crystals with Tunable Optical Properties Fabricated by Double Templating. Issue 37 (31st July 2017) - Sasaki, Yuji; Ueda, Motoshi; Le, Khoa V.; Amano, Reo; Sakane, Shin; Fujii, Shuji; Araoka, Fumito; Orihara, Hiroshi
Abstract : Self‐organized nano‐ and microstructures of soft materials are attracting considerable attention because most of them are stimuli‐responsive due to their soft nature. In this regard, topological defects in liquid crystals (LCs) are promising not only for self‐assembling colloids and molecules but also for electro‐optical applications such as optical vortex generation. However, there are currently few bottom‐up methods for patterning a large number of defects periodically over a large area. It would be highly desirable to develop more effective techniques for high‐throughput and low‐cost fabrication. Here, a micropixelated LC structure consisting of a square array of topological defects is stabilized by photopolymerization. A polymer network is formed on the structure of a self‐organized template of a nematic liquid crystal (NLC), and this in turn imprints other nonpolymerizable NLC molecules, which maintains their responses to electric field and temperature. Photocuring of specific local regions is used to create a designable template for the reproducible self‐organization of defects. Moreover, a highly diluted polymer network (≈0.1 wt% monomer) exhibits instant on–off switching of the patterns. Beyond the mere stabilization of patterns, these results demonstrate that the incorporation of self‐organized NLC patterns offers some unique and unconventional applications for anisotropic polymer networks. Abstract : An anisotropic polymer network with a micropixelated structure is fabricated by photopolymerization of a self‐organized pattern of a nematic liquid crystal (NLC). It is demonstrated that the network in turn imprints other nonpolymerizable NLC molecules, which maintains their responses to electric field and temperature. Various applications are introduced depending on the concentration of the polymer network.